A MONOPOLE-LIKE CLASSICAL SOLUTION TO A PURELY FERMIONIC MODEL OF EVEN DIMENSIONS - DIBEKCI, D; HORTACSU, M; KALAYCI, J; OZBEK, H (KLUWER ACADEMIC PUBL, 1991)
We present a static solution to the classical field equations of a purely spinorial model with SO(2n) internal symmetry in 2n dimensions. The model contains composite vector fields which have solutions of the Wu-Yang monopole type.
Keywords: COMPOSITE GLUONS; MAGNETIC MONOPOLES; SPINOR MODEL; FIELD-THEORY; INSTANTONS; Physics